PROSPECTS FOR THE DEVELOPMENT OF PEDIATRIC SCIENCE IN UZBEKISTAN IN THE YEARS OF INDEPENDENCE (Conferencea, 2024)
From the first days of independence in Uzbekistan, the protection of children's health, the field of pediatrics were defined as one of the important directions of state policy.